Answer:
43 and 5
Step-by-step explanation:
Let's let the two unknown numbers be a and b.
Their sum is 48, therefore:
![a+b=48](https://tex.z-dn.net/?f=a%2Bb%3D48)
And their difference is 38. In other words:
![a-b=38](https://tex.z-dn.net/?f=a-b%3D38)
We now have a system of equations. To solve, we can use substitution. First, add b to both sides in the second equation:
![a=38+b](https://tex.z-dn.net/?f=a%3D38%2Bb)
Substitute this into the first equation:
![(38+b)+b=48](https://tex.z-dn.net/?f=%2838%2Bb%29%2Bb%3D48)
Combine like terms:
![2b+38=48](https://tex.z-dn.net/?f=2b%2B38%3D48)
Subtract 38 from both sides:
![2b=10](https://tex.z-dn.net/?f=2b%3D10)
Divide both sides by 2:
![b=5](https://tex.z-dn.net/?f=b%3D5)
So, one of the numbers is 5.
The sum of them is 48. Therefore, the other number is 48-5 or 43.
So, our two numbers are 43 and 5.
And we're done!